Legal and policy measures to overcome public information lock down in Malaysia / Haswira Nor Mohamad Hashim, Anida Mahmood and Nurul Shuhada Suhaimi - Mohamad Hashim, Haswira Nor; Mahmood, Anida; Suhaimi, Shuhada (Faculty of Administrative Science & Policy Studies (FASPS), Universiti Teknologi MARA (UiTM) Shah Alam, 2018)
This paper reports a study that proposed legal and policy measures to overcome public information lock down in Malaysia. Public information lock down refers to the presence of the laws which impede citizens’ right to impart public sector information. Previous studies have identified public information lock down arising from legislations which impede citizens’ right to impart information. Despite the presence of Whistleblower Protection Act 2010, the Act prohibits direct public disclosure and the right is subject to other written laws currently in force in Malaysia. This study compared the laws and policies from several countries to identify the legal and policy measures to overcome public information lock down. A survey was conducted among respondents from government and non-governmental bodies to gain feedback on the most appropriate legal and policy measures to overcome public information lock down in Malaysia. The proposed measures are suitable for adoption to overcome public information lock down in Malaysia.